The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s10295-010-0844-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soya lecithin on the enzymatic system of the white-rot fungi Anthracophyllum discolor

Abstract: The present work optimized the initial pH of the medium and the incubation temperature for ligninolytic enzymes produced by the white-rot fungus Anthracophyllum discolor. Additionally, the effect of soya lecithin on mycelial growth and the production of ligninolytic enzymes in static batch cultures were evaluated. The critical micelle concentration of soya lecithin was also studied by conductivity. The effects of the initial pH (3, 4, and 5) and incubation temperature (20, 25, and 30°C) on different enzymatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…The result shows that SL had certain effect on the solubilization of PCP either below or above its CMC, 0.61 g•L −1 [30]; the solubilization was higher than when the SL concentration was above its CMC. Similar result was reported by Eddouaouda et al [34].…”
Section: The Pcp Solubilization Testmentioning
confidence: 81%
See 3 more Smart Citations
“…The result shows that SL had certain effect on the solubilization of PCP either below or above its CMC, 0.61 g•L −1 [30]; the solubilization was higher than when the SL concentration was above its CMC. Similar result was reported by Eddouaouda et al [34].…”
Section: The Pcp Solubilization Testmentioning
confidence: 81%
“…Information about the effect of SL on degrading microorganisms is limited. However, Bustamante et al [30] found that the increase in SL concentration caused an increase in mycelia growth of A. discolor. Besides, Soeder et al [25] found that SL enhanced growth of the bacteria under all conditions evaluated of surfactant concentrations.…”
Section: Effect Of Sl On Fungal Surface Of a Discolor Visualized By Semmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, laccase is obtained from organisms such as fungi. However, the low growth rates of these organisms and the low activity of these naturally derived cannot meet the market demand (Bustamante et al, 2011;Cañas and Camarero, 2010). In recent years, more attention has been focused on recombinant laccase (Ranieri et al, 2009), the yield of recombinant laccase, which could be increased significantly.…”
Section: Introductionmentioning
confidence: 99%